Multi-objective Optimization Model for Medical Waste Supply Chain Management Without Landfill Tax During COVID-19 In Indonesia - Vionanda, Aurellya; Chaerani, Diah; Nahar, Julita (Jurnal Matematika Integratif, 2024)
The COVID-19 pandemic has brought various problems into our daily life, and one of them is an increase in the volume of medical waste, which poses a risk to the environment and health.An evaluation of how optimal the supply chain management of medical waste as a whole can assist in the development of medical waste management and policy making.  In this paper, the  study on observing and reformulating the existing medical waste supply chain optimization model using Mixed Integer Linear Programming (MILP) is discussed. This study is done by modifying the objective function and the constraints with considering elimination of the landfill tax variable. The resulted model is also a multi-objective optimization problem. To this end, the Lexicographic Method is employed to obtained the optimal solution. In this model, the most prioritizes that is considered in the environmental condition to the medical waste supply chain. A numerical experiment is done in this paper which it results suggests two things, first, the cost of medical waste processing is much greater than its revenue, and second, the waste processing through incineration is not favorable. Thus, it can be concluded that this study provides a modified medical waste optimization model and decisions in determining the combination of the amount and method for each subtype of medical waste to be processed by maximizing profit and the amount of waste sent to the landfill.